2019
DOI: 10.3390/nu11040796
|View full text |Cite
|
Sign up to set email alerts
|

A Lipophilic Fucoxanthin-Rich Phaeodactylum tricornutum Extract Ameliorates Effects of Diet-Induced Obesity in C57BL/6J Mice

Abstract: Phaeodactylum tricornutum (P. tricornutum) comprise several lipophilic constituents with proposed anti-obesity and anti-diabetic properties. We investigated the effect of an ethanolic P. tricornutum extract (PTE) on energy metabolism in obesity-prone mice fed a high fat diet (HFD). Six- to eight-week-old male C57BL/6J mice were switched to HFD and, at the same time, received orally placebo or PTE (100 mg or 300 mg/kg body weight/day). Body weight, body composition, and food intake were monitored. After 26 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Fucoxanthin has a unique structure compared to other carotenoids like beta-carotene due to its allenic bond, conjugated carbonyl group, 5,6-monoepoxideand carbonyl group. Because of its structure, fucoxanthin has anti-inflammatory, anti-carcinogenic, anti-obesity and anti-diabetic properties [12,[16][17][18][19][20][21]. Therefore, fucoxanthin is supposed to prevent and alleviate several chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoxanthin has a unique structure compared to other carotenoids like beta-carotene due to its allenic bond, conjugated carbonyl group, 5,6-monoepoxideand carbonyl group. Because of its structure, fucoxanthin has anti-inflammatory, anti-carcinogenic, anti-obesity and anti-diabetic properties [12,[16][17][18][19][20][21]. Therefore, fucoxanthin is supposed to prevent and alleviate several chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…All these genes were downregulated when Euglena extract was present in the medium, showing that its inhibitory effect on adipocyte-differentiation was caused by repressing the early stage of adipocyte-differentiation. These observations were confirmed when adipogenesis was evaluated by determining Oil Red O from cells treated with 20% of extract during adipocyte-differentiation (days 0-7) and from those cells treated during adipocyte maturation (days [8][9][10][11][12][13][14]. Constant supplementation (day 0-14) with Euglena extract inhibited lipid accumulation by approximately 50% as compared to the control cells.…”
Section: Figurementioning
confidence: 55%
“…Finally, Gille et al [11] incubated 3T3-L1 cells on day 7 of differentiation with an ethanolic extract of the same microalga, at a dose of 100 mg/L for 24 h. Moreover, they also tested its bioactive compound fucoxanthin at a concentration of 5 µM. According to the authors, each 100 mg/L of the microalga contained 3.6 µM of fucoxanthin.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that fucoxanthin reduces the body weight and the epididymal fat weight in diabetic mice, upregulates the expression of AKT and Adenosine 5 -monophosphate-activated protein kinase (AMPK), downregulates the expression of GSK3, reduces plasma TG and TC levels, and improves lipid metabolism in diabetic mice [55]. Others have shown that fucoxanthin reduces body fat in mice induced by HFD, decreases lipid uptake and turnover in visceral WAT while upregulating the expression of related genes key to fatty acid oxidation and thermogenesis (CPT1, UCP1) in subcutaneous WAT and enhances UCP1 protein in interscapular brown adipose tissue to ease the accumulation of fat caused by HFD [59]. Fucoxanthin's ability to reduce body weight, BMI and abdominal fat and to improve body fat status by acting on visceral and subcutaneous fat is shown in the research conducted [60].…”
Section: Fucoxanthinmentioning
confidence: 99%